2019
DOI: 10.21873/invivo.11742
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia Mouse Genotype-specific Mitigation of Total Body Irradiation by GS-Nitroxide JP4-039

Abstract: Background/Aim: Radiation mitigator, GSnitroxide, JP4-039, was evaluated for mitigation of total body irradiation (TBI) in Fanconi anemia (FA) Fancd2 −/− (129/Sv), Fancg −/− (B6), and Fanca −/− (129/Sv) mice. Materials and Methods: JP4-039 dissolved in 30% 2hydroxypropyl-β-cyclodextrin was injected intramuscularly 24 h after total body irradiation (9.25 Gy) into Fanca −/− , Fancd2 −/− and Fancg −/− mice. Irradiation survival curves were performed in vitro using bone marrow stromal cell lines derived from Fanca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Consistent with this notion, we observed enhanced mitochondrial ROS production in FAN1KO RTECs but not in untreated or parental cells 48 h after short-term exposure to low-dose cisplatin by using MitoSox staining ( Figure 3 E,F), which detects mitochondrial superoxide, a specific product of OXPHOS. In contrast, when the cells were treated with the mitochondrially targeted ROS and electron scavenger JP4-039 [ 40 , 41 , 42 ] immediately after exposure to cisplatin, we observed a significant reduction in the accumulation of mitochondrial ROS in FAN1KO hRTECs ( Figure 3 E,F), further demonstrating that FAN1 inactivation leads to increased susceptibility to mitochondrial functional impairment in RTECs. Consistent with the increase in mitochondrial ROS, cisplatin-treated FAN1KO cells displayed a significant upregulation in total cellular ROS, as measured by CM-H2DCFDA and CellROX staining ( Supplementary Figure S4A,B ).…”
Section: Resultsmentioning
confidence: 84%
“…Consistent with this notion, we observed enhanced mitochondrial ROS production in FAN1KO RTECs but not in untreated or parental cells 48 h after short-term exposure to low-dose cisplatin by using MitoSox staining ( Figure 3 E,F), which detects mitochondrial superoxide, a specific product of OXPHOS. In contrast, when the cells were treated with the mitochondrially targeted ROS and electron scavenger JP4-039 [ 40 , 41 , 42 ] immediately after exposure to cisplatin, we observed a significant reduction in the accumulation of mitochondrial ROS in FAN1KO hRTECs ( Figure 3 E,F), further demonstrating that FAN1 inactivation leads to increased susceptibility to mitochondrial functional impairment in RTECs. Consistent with the increase in mitochondrial ROS, cisplatin-treated FAN1KO cells displayed a significant upregulation in total cellular ROS, as measured by CM-H2DCFDA and CellROX staining ( Supplementary Figure S4A,B ).…”
Section: Resultsmentioning
confidence: 84%
“…FANCD2 regulates the expression of genes and/or proteins related to iron metabolism (such as FTH1, TF, TFRC, HAMP, HSPB1, SLC40A1, and STEAP3) and lipid peroxidation (such as GPX4). In addition, in vivo experiments have confirmed that the drug is less effective at inducing ferroptosis in FA mice, whereas the effect on control mice has been improved (Epperly et al, 2020). These data indicate that FANCD2 has an important role in combating ferroptosis in bone marrow mesenchymal stem cells, and FANCD2 may be a viable target for the development of new anticancer therapies to reduce the side effects of ferroptosis inducers.…”
Section: Fancd2mentioning
confidence: 77%
“…Radiation protective drugs have been developed to increase the therapeutic ratio of irradiation in animal models using transplantation of orthotopic tumors. Orthotopic tumors have been derived from wild type mice that do not have the FA genotype (25)(26)(27)(28)(29). Furthermore, the radiobiology of a mouse FA cancer cell line has not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has focused on methods to reduce the toxicity of chemoradiotherapy in patients with FA (20)(21)(22)(23)(24)(25)(26)(27). The development of new agents to protect normal tissues, while compromising the viability of residual tumor cells has already led to the discovery of novel radioprotective agents including the mitochondrial targeted nitroxide JP4-039 (23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%